2021
DOI: 10.1007/s00415-021-10848-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute and post-acute neurological manifestations of COVID-19: present findings, critical appraisal, and future directions

Abstract: Acute and post-acute neurological symptoms, signs and diagnoses have been documented in an increasing number of patients infected by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), which causes Coronavirus Disease 2019 (COVID-19). In this review, we aimed to summarize the current literature addressing neurological events following SARS-CoV-2 infection, discuss limitations in the existing literature and suggest future directions that would strengthen our understanding of the neurological seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
1
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 69 publications
2
45
1
12
Order By: Relevance
“…The evaluation of neurological manifestations in post-acute COVID-19 disease can be explained by the different populations taken as samples to address the problem. The COVID-19 is a very new disease and, at present, incomplete knowledge of the mechanism of infection and the complexity of viral and non-viral factors involved in the disease explain the incomplete information on the effects of the SASR-CoV-2 virus on the nervous system (Beghi et al 2022 ). Although the main symptoms of COVID affect the respiratory system, acute and subacute neurological manifestations during the infection have been described in over 35% of cases (Nolen et al 2022 ).…”
Section: Neurological Consequences Of Long-covid-19mentioning
confidence: 99%
“…The evaluation of neurological manifestations in post-acute COVID-19 disease can be explained by the different populations taken as samples to address the problem. The COVID-19 is a very new disease and, at present, incomplete knowledge of the mechanism of infection and the complexity of viral and non-viral factors involved in the disease explain the incomplete information on the effects of the SASR-CoV-2 virus on the nervous system (Beghi et al 2022 ). Although the main symptoms of COVID affect the respiratory system, acute and subacute neurological manifestations during the infection have been described in over 35% of cases (Nolen et al 2022 ).…”
Section: Neurological Consequences Of Long-covid-19mentioning
confidence: 99%
“…Also, it was discovered there are some factors related to acute COVID-19 which are linked with the higher probability of occurrence of post-COVID-19 complications and their severity. The severity and higher probability of occurrence of long-lasting COVID-19-related disturbances were found to be positively associated with the following factors associated with acute COVID-19: some specific acute symptoms (11, 12), severity (13, 14), and long duration of acute COVID- 19 (11) and high viral load (15). Vaccination status was associated with a lower risk of exacerbation of post-COVID-19 complications and with lower severity (16,17).…”
Section: Introductionmentioning
confidence: 98%
“…Clinical studies reported a high risk of N/P disorders in COVID-19 and post-COVID-19 patients and also found that their outcomes were positively associated with the severity of COVID-19. [8][9][10] These clinical manifestations occur due to the direct invasion of SARS-CoV-2 into the central nervous system (CNS), often complicated by systemic hypoxia, dysfunctional activity of the renin-angiotensin system and other relevant pathological changes. These changes may remain long term and persistently causing post-COVID-19 CNSrelated symptoms such as difficulties in memory, attention and focus, persistent headaches, lingering loss of sense of smell and taste, enduring muscle aches and chronic fatigue.…”
Section: Introductionmentioning
confidence: 99%